Limit and frailty: the exercise of chance and self-care in socio-medical training paths - Alessandra Augelli (University of Bologna, 2014)
Confronting with the limit and frailty of human existence is inevitable, and in such circumstances, healthcare professionals are often equipped with inadequate theoretical and technical tools. This may result in they having to rely on relational skills, which are by their very nature exposed to the typical risks of the situations they are facing, i.e. unpredictability, misunderstanding, refusal, failure. Criteria of certainty and programmability, which define exact sciences, cannot be transferred into the relationship level, nevertheless, significant resources can result from this gap, through which one can learn how to stay within the limit without hiding or refuting it. The phenomenological perspective, while bringing the focus back to the principle of adherence to the real world and to the transcendence principle, provides a focus on the acceptance of limits, not as sheer elements which cannot be eradicated, but as real spaces for growth and transformation. For this reason, continuing education paths ought to offer spaces where one can consider limit and frailty as chances to reassess experience and become increasingly aware of it together with the others. For their very nature, such paths would promote a productive wandering, intended as an opportunity to open oneself to novelties and to make sense of endless new situations.